A atuação do pedagogo no MST: revelações de um estudo exploratório - Georgia Sobreira dos Santos Cêa; Camila Ferreira da Silva; Samara Santos Marques de Gusmão; Thayanne Araújo Silva (EccoS – Revista Científica)
In 2006, the graduate programs in Pedagogy were defined as a degree that should provide the training of performance of the professional in schools and other spaces, including social movements. This paper aims to present a curricular experience called "integrated projects", which took as its object the performance of the teacher in Brazilian landless workers' movement (MST), and involved teachers and students of the second period of the course of Pedagogy at the Universidade Federal de Alagoas (UFAL). The article reflects on the importance of treatment of the relationship between social movements in education and training of teachers. It is presented a methodological course of the study, and it is also exposed a significant learning that it offers, with emphasis on understanding the relationship between the struggle for land and education, considering the actions taken by a teacher in the MST.